Soluble urokinase-type plasminogen activator receptor plasma concentration may predict susceptibility to high altitude pulmonary edema - Hilty, Matthias Peter; Zügel, Stefanie; Schoeb, Michele; Auinger, Katja; Dehnert, Christoph; Maggiorini, Marco (Mediators of inflammation, 2016)
Introduction. Acute exposure to high altitude induces inflammation. However, the relationship between inflammation and high altitude related illness such as high altitude pulmonary edema (HAPE) and acute mountain sickness (AMS) is poorly understood. We tested if soluble urokinase-type plasminogen activator receptor (suPAR) plasma concentration, a prognostic factor for cardiovascular disease and marker for low grade activation of leukocytes, will predict susceptibility to HAPE and AMS. Methods. 41 healthy mountaineers were examined at sea level (SL, 446 m) and 24 h after rapid ascent to 4559 m (HA). 24/41 subjects had a history of HAPE and were thus considered HAPE-susceptible (HAPE-s). Out of the latter, 10/24 HAPE-s subjects were randomly chosen to suppress the inflammatory cascade with dexamethasone 8 mg bid 24 h prior to ascent. Results. Acute hypoxic exposure led to an acute inflammatory reaction represented by an increase in suPAR ( at SL versus at HA, ), CRP ( at SL versus at HA, ), and IL-6 ( at SL versus at HA, ) in all subjects except those receiving dexamethasone. The ascent associated decrease in PaO2 correlated with the increase in IL-6 (, ), but not suPAR (, ); the increase in IL-6 was not correlated with suPAR (, ). Baseline suPAR plasma concentration was higher in the HAPE-s group ( versus , ); no difference was found for CRP and IL-6 and for subjects developing AMS. Conclusion. High altitude exposure leads to an increase in suPAR plasma concentration, with the missing correlation between suPAR and IL-6 suggesting a cytokine independent, leukocyte mediated mechanism of low grade inflammation. The correlation between IL-6 and PaO2 suggests a direct effect of hypoxia, which is not the case for suPAR. However, suPAR plasma concentration measured before hypoxic exposure may predict HAPE susceptibility.
Gesehen am 14.05.2020